Odpowiedzi

Najlepsza Odpowiedź!
2010-02-15T20:25:29+01:00
A) 1/3 * (*6x+9) - 4 = -5 (x+1)
2x + 3 - 4 = -5x - 5
2x + 5x = -5 -3 + 4
7x = -4
x = -4/7

b) 0,2 (10 - 5x) = 3+2 (x-1)
2 - x = 3 + 2x -2
-x - 2x = 3 - 2 - 2
-3x = -1
x = 1/3


c) 2x + 5 = 14,8 + (x*3)
2x + 5 = 14,8 + 3x
2x - 3x = 14,8 - 5
-x = 11,8
x = 11,8


zad2
a) 27-x = 35 / -27
-x = 8 / : (-1)
x = -8

b) 18 + x =17 / -18
x = -1

c) - 0,6 x=9 / : -0,6
x = 15
1 1 1
  • Użytkownik Zadane
2010-02-15T20:27:17+01:00
A) 1/3 * (*6x+9) - 4 = -5 (x+1)
2x+3-4=-5x-5
2x+5x=-3+4-5
7x=-4//7
x=-4/7

b) 0,2 (10 - 5x) = 3+2 (x-1)
2-x=3+2x-2
-x-2x=-2+3-2
-3x=1//-3
x=-1/3

c) 2x + 5 = 14,8 + (x*3)
2x+5=14,8+3x
2x-3x=-5+14,8
-x=9,2//-1
x=9,2



2
a) 27-x = 35
-x=-27+35
-x=8//-1
x=-8

b) 18 + x =17
x=-18+17
x=-1
c) - 0,6 x=9/10
-6x=90//-6
x=-15


mam nadzieje ze pomoglam. pozdrawiam. i licze na naj .;P